Addressing the other : a three language study in power, personal relations, and second person pronouns - Siriwardena, Regi.; International Centre for Ethnic Studies (Colombo, Sri Lanka : International Centre for Ethnic Studies, 1992)
Study of second person pronouns in English, Russian, and Sinhala.
Includes bibliographical references (p. 74-75).
Keywords: English language -- Pronoun; Russian language -- Pronoun; Sinhalese language -- Pronoun; English language -- Social aspects; Russian language -- Social aspects; Sinhalese language -- Social aspects; Sociolinguistics; Speech acts (Linguistics); Forms of address